Differences in Knowledeges and Attitudes Of Adolescents Before and After Being Given Health Promotion Regarding The dangers of Free Sex - Kusumawardani, Paramitha Amelia (Universitas Islam Lamongan, 2022)
Abortion and pregnancy are examples of unwanted things that arise as a negative result of free-sex behavior in adolescents. The knowledge and attitudes of adolescents will be influenced by the lack of information regarding reproductive health in adolescents. In addition, other factors that can affect the knowledge and attitudes of adolescents are health education by schools and local health workers. The aim of the study was to find out the knowledge and attitudes of adolescents before and after receiving health promotion about the language of free sex in Suko village. The research method used is descriptive with a cross-sectional design. Sampling technique with purposive sampling. The study population consisted of 68 men adolescents and women in Suko village in October-November 2022. The results showed that before health promotion was given, adolescent knowledge was sufficient (55.9%) and after it was given it was good (89.7%). The attitude of adolescents before giving health promotion had a positive attitude (52.9%) and after being given it increased (75.0%). The conclusion of the study is that there is an increase in the knowledge and attitudes of adolescents after being given health promotion regarding the dangers of free sex.